Metabolomics analysis of the protective effect of rubusoside on palmitic acid-induced lipotoxicity in INS-1 cells using UPLC-Q/TOF MS. (9th May 2019) - Zheng, Hua; Wu, Jinxia; Huang, Hong; Meng, Chunmei; Li, Weidong; Wei, Tianli; Su, Zhiheng
Abstract : Diabetes is one of the most severe chronic diseases worldwide. Abstract : Diabetes is one of the most severe chronic diseases worldwide. It is widely accepted that apoptosis of the pancreatic beta cell is an important cause for the induction of hyperglycemia and high levels of free fatty acids (FFAs), also called lipotoxicity associated with pancreatic beta cell dysfunction. Lipotoxicity has been proven to be an important pathogenic factor of diabetes. However, until now, the mechanism of FFA-induced lipotoxicity in INS-1 cells has not been fully understood. Current anti-diabetic drugs that protect islet cells are often toxic to healthy cells, resulting in negative side effects. Thus, there is an urgent need to identify more effective and safer anti-diabetic agents to protect pancreatic islet cells. Rubusoside (RUB) is a major ingredient in the leaves of Rubus suavissimus S. Lee, which decreases blood glucose levels by protecting pancreatic islet cells. However, the exact mechanism of this effect is unknown. In this study, metabolomics experiments based on UPLC-Q/TOF MS characterized a total of 15 metabolites as potential biomarkers associated with lipotoxicity induced by palmitic acid in INS-1 cells. According to the metabolic pathway analysis, pentose and glucuronate interconversions, and glycerophospholipid metabolism were recognized as the most influenced metabolic pathways associated with lipotoxicity. Unexpectedly, deviations of 14 metabolites in lipotoxic INS-1 cells were regulated by RUB, suggesting synergistic mediation of the abnormal metabolic pathways. The metabolomics strategy based on UPLC/Q-TOF MS analysis provides a new insight into the mechanisms of lipotoxicity induced by palmitic acid and the anti-lipotoxic activity of RUB in INS-1 cells.